2017
DOI: 10.1111/1759-7714.12524
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive esophagectomy in the lateral‐prone position: Experience of 124 cases in a single center

Abstract: BackgroundMinimally invasive esophagectomy was first introduced as a new technique for esophageal cancer treatment 20 years ago. Performing this procedure in the lateral‐prone position is the most appropriate method. Since May 2013, our center has performed 124 esophageal cancer operations using this procedure. Herein, we share our experience.MethodsWe retrospectively reviewed 124 consecutive patients who had received minimally invasive esophagectomy in the lateral‐prone position from May 2013 to June 2017. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
2
9
1
2
Order By: Relevance
“…All 82 esophagectomy cases were performed successfully with the MIME procedure. Operative time was 260 min and blood loss was 100 ml, which were similar to the results in other studies (Meng et al, 2014;Ma et al, 2018). A previous study reported that blood loss during MIE was less than that during OE, but the operative time was not shorter than that in OE (Lv et al, 2016).…”
Section: Learning Curvesupporting
confidence: 88%
See 1 more Smart Citation
“…All 82 esophagectomy cases were performed successfully with the MIME procedure. Operative time was 260 min and blood loss was 100 ml, which were similar to the results in other studies (Meng et al, 2014;Ma et al, 2018). A previous study reported that blood loss during MIE was less than that during OE, but the operative time was not shorter than that in OE (Lv et al, 2016).…”
Section: Learning Curvesupporting
confidence: 88%
“…In our 82 cases, the total complication rate was 24.4%, which was much lower than previously reported for open esophagectomy (OE) (Low et al, 2015) and MIE (Ma et al, 2018). Anastomotic leakage was the major complication of esophagectomy, and occurred in 4.9% of our cases.…”
Section: Fig 4 Learning Curve Of Mime At I and Ii Stagescontrasting
confidence: 47%
“…Most reports have used intraoperative variables, such as operative time (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), but other reports have also used clinically more relevant outcome parameters, such as postoperative complications and anastomotic leakage (13,14,19). Regarding analysis methods, most studies assigned patients to arbitrarily created groups and compared outcomes of patients operated on early after implementation between patients operated on later (9,11,(20)(21)(22)(23)(24)(25)(26)(27). Other studies used cumulative sum (CUSUM) analysis or variations of CUSUM and therefore omitted splitting a patient population in arbitrarily created groups (6,8,10,11,14,16,18,19).…”
Section: Learning Curve Of Miementioning
confidence: 99%
“…This could be due to the small sample size. For some authors, the learning curve to reach a plateau ranges between 15 and 20 cases, while other authors who worked with systematized cumulative measurement systems reported > 35 or 40 cases 8,[27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…Esto podría deberse al tamaño reducido de la muestra. Para algunos autores, los casos necesarios para alcanzar la meseta en la curva de aprendizaje oscilan entre 15 y 20; para otros, que trabajaron con sistemas de mediciones acumulativos y sistematizados, el número debe ser mayor de 35 o 40 8,[27][28][29][30][31] .…”
Section: Movilización Esofágicaunclassified